Clioquinol reduces tau phosphorylation and oligomerization: Molecular and cell biology/tau. (7th December 2020) - Zhu, Feiyan; Lin, Gaoping; Hamano, Tadanori; Kanaan, Nicholas M.; Yen, Shu‐Hui; Asano, Rei; Shirafuji, Norimichi; Sasaki, Hirohito; Enomoto, Soichi; Yamaguchi, Tomohisa; Ueno, Asako; Ikawa, Masamichi; et al.
Abstract: Background: The pathological features of AD are neurofibrillary tangles (NFTs) composed of highly phosphorylated tau and senile plaques (SPs) composed of amyloid β protein (Aβ). It was suggested that Cu 2 + induced hyperphosphorylation of tau and Zn 2 + deposits on SPs. Clioquinol (CQ) has a mild chelating effect on Zn 2 + and Cu 2 + . In addition, CQ has been shown to reduce Aβ aggregation by removing Zn 2+ from SPs. However, the effect of CQ on tau aggregation is not fully understood. The purpose of our study is to examine the effect of CQ on tau metabolism by using a cell culture model of tauopathy. Methods: Human neuroblastoma cell line M1C cells that express wild‐type tau protein (4R0N) via tetracycline (Tet) off induction was used. M1C cells were exposed to 0.1‐10 μM CQ on day 4 of Tet‐Off induction, and harvested at the end of Day 5. Total tau detected by Tau5, and phosphorylated tau detected by PS199/202, AT180, AT270, CP13, and PHF‐1 antibodies, were examined using Western blot analysis. Immunocytochemical studies, fractional analysis and immunoprecipitation of ubiquitinated tau were also performed. Tau kinases including c‐Jun N‐terminal kinase (JNK), and P38 MAPK and tau phosphatase, protein phosphatase 2A (PP2A) were also examined. C‐terminal truncated pathological tau was detected by using the antibody TauC3. In addition, autophagy and proteasome activity were also examined. Result: Phosphorylated tau levels were reduced by 1‐10 μM CQ treatment. Tau kinases, JNK and p38 MAPK were inactivated by CQ treatment. Interestingly, activation of the tau phosphatase PP2A was also observed with CQ treatment. Fractionation studies showed that CQ treatment reduced AT180 and AT270 positive high molecular weight tau in the Tris‐insoluble, sarkosyl‐soluble fraction. CQ also reduced tau oligomer specific antibody TOC1‐positive oligomeric tau. CQ reduced caspase‐cleaved tau detected by antibody TauC3. P62 levels were reduced by CQ treatment, suggesting that CQ activates autophagy. In addition, CQ slightly reduced high molecular weight ubiquitinated tau. This implies activation of the ubiquitin‐proteasome by CQ. Conclusion: CQ could provide beneficial effects against pathogenic forms of tau via multiple mechanisms and may represent a viable therapeutic approach for AD and other tauopathies.